Identification and Quantification of Estrogenic Chemicals in Coffee Prepared from Capsules Using Ultra-Performance Liquid Chromatography with Tandem Mass Spectrometry. (29th May 2020) - Sakaki, Junichi; Melough, Melissa; Provatas, Anthony; Perkins, Christopher; Chun, Ock
Abstract: Objectives: Estrogenic chemicals (ECs) are harmful compounds that can leach from plastic, particularly when under high temperature or pressure. Capsule coffee, coffee brewed from a single-serve coffee machine using a pre-packed plastic capsule, is becoming popular but there are concerns that it may increase exposure to ECs. Therefore, the objective of this study was to identify and quantify the ECs in capsule coffee extracts and compare them to the ECs present in coffee extracts prepared using a method devoid of plastic. Methods: Twenty-two top-selling varieties of plastic capsule coffee from 4 popular brands were brewed and 15 equivalent varieties of whole bean and ground coffee were brewed using a stainless-steel French press and used as controls. ECs were then extracted from the capsule samples and controls with liquid-liquid extraction. The ultra-performance liquid chromatography with tandem mass spectrometry analytical method was used to identify and quantify ECs in coffee extracts after testing its validity. Results: Benzophenone was the most frequently detected EC among the 22 capsule coffee samples, evident in six samples, followed by bisphenol A (four), dibutyl phthalate (three), 4-nonylphenol (three) and bisphenol F (two). Di(2-ethylhexyl) phthalate, caprolactam, bisphenol S and dimethyl terephthalate were either not detected or detected in quantities below the method detection limit. In seven instances the concentration of ECs in capsule coffees was greater than that of coffee prepared from the French press while in five instances the opposite trend was observed. The total exposure to ECs from either capsule coffee or coffee prepared from the French press was well below that of safety guidelines. Conclusions: These results indicate that consuming plastic capsule coffee likely increases exposure to ECs compared to coffee brewed without plastic. Future studies are needed to evaluate the estrogenic activities of capsule coffee in vitro and determine whether EC content is a valid predictor of estrogenic activity. Funding Sources: This study was supported by the National Institutes of Health.